Review: Pork production with maximal nitrogen efficiency. (25th October 2017) - Millet, S.; Aluwé, M.; Van den Broeke, A.; Leen, F.; De Boever, J.; De Campeneere, S.
Abstract : During growth, pigs convert plant protein into animal protein. The major part of the ingested protein is excreted via manure, with potential nitrogen (N) losses to the environment. To limit N losses and increase sustainability of pork production, the efficiency of protein conversion should be maximized. The aim of this paper is to critically evaluate diet and management strategies linked with N efficiency. Besides nutrition, we discuss three management strategies observed in science and in practice to be linked with improved N efficiency: genetic selection, castration and slaughter weight. Because diet has a marked effect on eventual N losses, it must also be taken into account when evaluating management strategies. A reductionist approach, such as feeding the same diet across all management treatments, may overestimate the effect of a management strategy and eventually lead to incorrect conclusions. The amount of excreted N depends on the amount of ingested N, the amount of absorbed N, the amino acid (AA) balance in the diet and the animal's N and AA requirements. Daily multiphase feeding adapted to the individual animal's AA needs is likely to be the most N efficient. For animals housed in groups, phase feeding is necessary. When combined with periods of temporary AA restriction, N efficiency can be further improved. Specific AA consumption must be balanced by applying the ideal protein concept. With better knowledge of the requirements of individual animals and the commercial availability of certain AAs, the total dietary CP level can be lowered within limits. Further research is needed on the minimal CP level that allows maximal performance. For this end a useful parameter may be the ratio of standardized ileal digestible (SID) lysine : apparent total tract digestible CP level. By combining optimal nutrition and management, a whole body N efficiency approaching 60% may be achievable in the near future.